Mejoramiento de la producción y comercialización de banano en la parroquia rural Tenguel cantón Guayaquil - Saltos Saltos, Viviana Vicenta (2017)
The following work focuses on the banana's productive growth, which aims to improve and increase the levels of agricultural production in the "San Rafael" hacienda in the Tenguel Rural Parish located in the canton of Guayaquil. Of banana production, to determine what are the main problems blocking banana development in the "San Rafael" hacienda, and to analyze and establish what strategy would be appropriate for the hacienda to achieve a better yield in banana agricultural production And thus have a growth in the marketing of the product………